A Critical Assessment Of Efforts To Identify The Revelation With The Language Of The Revelation In The Context Of Religious Philosophy - Taş, Nusret (Fırat University, 2022)
In this study, the works of scholars and thinkers whose views on the subject critically evaluated are taken into account. In addition, scientific articles, encyclopedia articles, books and book chapters written by some researchers who are thought to be related to the subject are also used. In this study, a subject-centered literature review is conducted. The data are collected, classified, analyzed and mutually evaluated. In the introductory part of the study, theories about the emergence, development and differentiation of language in general are emphasized. In this context, both the expressions of the holy books on the subject and the examples from the philosophical theories are discussed. In this context, the evidence put forward by those who blessed the language of revelation by identifying it with revelation itself is tried to be determined and evaluated. Here, there are views that both bless and oppose Arabic. Finally, the narrative and rational justifications of those who defend this theory are evaluated. According to the data obtained within the scope of the study, some Muslim scholars and thinkers who belong to different scientific traditions such as language, literature, tafsir, kalam, fiqh, hadith and philosophy have made an effort to sanctify the language of revelation as revelation. However, they had difficulty in justifying their views on the subject. For this reason, the effort to identify the language of revelation with revelation has not been generally accepted in the Islamic world.

İslam düşünce tarihinin ilk dönemlerinde vahyin dilini vahiyle özdeşleştirme ve kutsama amacını taşıyan birtakım çabalara tanık olunmaktadır. Bir şekilde bu çaba içinde olanlar arasında İmam Şafiî (öl. 820) gibi fakihler, İbn Kuteybe (öl. 889) ve İbn Fâris (öl. 1004) gibi dil bilginleri, el-Bâkıllânî (öl. 1013) gibi kelamcılar, en-Nîsâbûrî (öl. 1014) gibi hadisçiler ve Fahreddin er-Râzî (öl. 1210) gibi tefsirciler yer aldığı gibi İhvân-ı Safâ (X. yüzyıl) gibi İslam felsefecileri de yer almaktadır. Bu düşünceyi savunanlar, genel olarak Arap diline atıf yapan bazı Kur’ân ayetlerini zorlama yoruma tabi tutmakta, ayrıca sıhhat derecesi tartışmalı olan ve hadisçilerin çoğunluğu tarafından güvenilmez olarak kabul edilen bazı hadis rivayetlerini kullanmaktadırlar. İslam felsefecileri arasında yer alan ve akıl ile vahyi uzlaştırma gayretinde olan İhvân-ı Safâ ise konuyla ilgili düşüncelerini temellendirmek için hem Kur’ân ayetlerini zorlama yoruma tabi tutmakta hem de varlık düzeniyle ilgili bazı felsefî düşünce teorilerine başvurmaktadır. Bu çalışmanın amacı, genel olarak vahyin dilini de vahiy gibi kutsamaya çalışan isimleri anılan Müslüman âlim ve düşünürlerin konuyla ilgili görüşlerini din felsefesi bağlamında eleştirel bir değerlendirmeye tabi tutmaktır.
Vahyin Dilini Vahiyle Özdeşleştirme Çabalarına Din Felsefesi Bağlamında Eleştirel Bir Değerlendirme
Keywords: Religious Studies; Din Araştırmaları